2017
DOI: 10.12973/ejmste/77042
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Model and Measuring Tool for Specialists Accreditation in Area of Public Health Services

Abstract: The main purpose of the paper is to present some theoretical approaches and some methods providing assessment optimization in specialists' accreditation in area of public health services. The results of research presented in this paper, include the model of multistage adaptive measurements and two methods for reliability and validity analysis, providing high justice decisions in accreditation and corresponding to requirements in High-Stakes Testing procedures. The assessment optimization intends for minimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Для тестирования испытуемых при аккредитации используется единая база оценочных средств, формируемая методическим центром аккредитации специалистов и структурированная в соответствии с трудовыми функциями профессиональных стандартов по соответствующим специальностям [10].…”
Section: Medical Educationunclassified
“…Для тестирования испытуемых при аккредитации используется единая база оценочных средств, формируемая методическим центром аккредитации специалистов и структурированная в соответствии с трудовыми функциями профессиональных стандартов по соответствующим специальностям [10].…”
Section: Medical Educationunclassified
“…The third stage is the assessment of the level of Sizova et al / Fairness Principle in Accreditation of Health Specialists: The Differential Item Functioning Method 2 / 8 mastering the labor functions of professional standards using situational tasks. Based on the results of the successful implementation of the three stages, a decision is made to issue an accreditation certificate (Aydarov & Krasilnikov, 2017;Semenova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These authors showed that there is a small amount of school climate studies regarding the adaptation process of questionnaires Similar results were found in studies with a different focus. [33][34][35][36][37]…”
Section: Introductionmentioning
confidence: 99%